Penguatan Quality of Work Life untuk Pekerja Migran Indonesia di Hong Kong Berbasis Komunitas dan Psikoedukasi - Anwar, Saiful; Utaminingsih, Sri; Indayani, Rin; Cheng Cristina , Batseva (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service is an implementation of research entitled The Influence of Quality of Work Life and Organizational Culture on Professional Commitment. Indonesian Migrant Workers are one of the backbones of the national economy and Hong Kong is one of the main destinations for migrant workers from Indonesia. The migrant worker community and civil society organizations in Hong Kong play a crucial role in assisting Indonesian migrant workers. In this context, the role of the community, non-governmental organizations, and the state is crucial in efforts to improve the quality of life and work of Indonesian migrant workers. The Indonesian migrant community in Hong Kong has demonstrated high solidarity through educational, spiritual, and advocacy activities. Through a structured and participatory online workshop approach, it is hoped that the quality of life and work of Indonesian migrant workers in Hong Kong can be significantly improved. Not only does this program provide knowledge and skills, it also serves as an empowerment space that builds solidarity, self-confidence, and personal resilience in facing the challenges of life abroad Keywords: Quality Of Work Life; Indonesian Migrant Workers; Community; Psychoeducation